Plasma carnitine ester profile in adult celiac disease patients maintained on long-term gluten free diet - Bene, Judit (World J Gastroenterol, 2005)
AIM: To determine the fasting plasma carnitine ester in patients with celiac disease. METHODS: We determined the fasting plasma carnitine ester profile using ESI triple quadrupol mass spectrometry in 33 adult patients with biopsy-confirmed maturity onset celiac disease maintained on long term gluten free diet. RESULTS: The level of free carnitine did not differ as the celiac disease patients were compared with the healthy controls, whereas the acetylcarnitine level was markedly reduced (4.703 ± 0.205 vs 10.227 ± 0.368 nmol/mL, P<0.01). The level of propionylcarnitine was 61.5%, butyrylcarnitine 56.9%, hexanoylcarnitine 75%, octanoylcarnitine 71.1%, octenoylcarnitine 52.1%, decanoylcarnitine 73.1%, cecenoylcarnitine 58.3%, lauroylcarnitine 61.5%, miristoylcarnitine 66.7%, miristoleylcarnitine 62.5% and oleylcarnitine 81.1% in the celiac disease patients compared to the control values, respectively (P<0.01). CONCLUSION: The marked decrease of circulating acetylcarnitine with 50-80 % decrease of 11 other carnitine esters shows that the carnitine ester metabolism can be influenced even in clinically asymptomatic and well being adult celiac disease patients, and gluten withdrawal alone does not necessarily normalize all elements of the disturbed carnitine homeostasis.